Community Perception on Village Government Performance in Handling Covid-19 in Tarlawi Village - muhsanan muhsanan (Eduvest - Journal of Universal Studies, 2021)
This study aims to find out how the public perception of the performance of the village government in handling covid-19 in Tarlawi Village. The research used in this study is descriptive with quantative approach. The population in the study amounted to 342 which was clarified based on the number of heads of families (KK) with a sample of 185 people using random sampling. Data collection techniques are observation, interview, questionnaire and library study. Data analysis techniques used are validity test, reliability test and T-test one sample with the process using statistical product and service solution (SPSS) version 21 program. The results showed that the public perception of the performance of the Village government in handling covid-19 in Tarlawi Village is less than 75% meaning that it gives a bad response.